Protecting the ideological foundation of the party, fighting against wrong and hostile views in the current period - Bùi Thị Bích Thuận (Tạp chí Nghiên cứu Khoa học Công đoàn, 2023)
Currently, hostile forces are trying to sabotage and distort Marxism-Leninism, Ho Chi Minh's thought, attacking the ideological foundation of the Party in order to reduce the people's confidence in the Party's leadership and the management of the State. In the face of this situation, protecting the ideological foundation of the Party and fighting against wrong and hostile views is an important task, vital in the defense of the Party, the State, the People and the socialist regime. Propagating, educating and protecting the ideological foundation of the Communist Party of Vietnam is the central and regular content of party building in terms of ideology and politics. Therefore, the article aims to contribute to clarifying the ideological foundation of the Party, identifying the plots and tricks of hostile forces and policies and solutions to protect the ideological foundation of the Party in the current period.